PROSEDUR PENCATATAN UTANG USAHA PADA PT. A - Julia Putri (2021)
The purpose of writing this Final Project is to provide information on how to record trade payables in an entity (PT. A) which is engaged in the processing industry. The procedure for presenting accounts payable information in the statement of financial position is of course strongly influenced by the information system and standard operating standards owned by the company, as well as reliable human resources in the accounting field. Information on the procedure for presenting this trade payable as a result of the purchase of credit for raw materials. Information starts from recording the acknowledgment of accounts payable to recording the payment of accounts payable by the accounting department. The presentation of information aims to ensure that all trade payables have been recognized and paid for as well as to safeguard the company's assets. The information system used by PT. A is a Jurnal.id application and maximizes spreadsheets. The departments related to the presentation of accounts payable information are the purchasing department, accounting department and production department, the build up voucher procedure method as a method of recording accounts payable is used by PT A to maintain information accountability to all stakeholders. Keywords : Accounts Payable Financial Information, Accounts Payable Recording, Accounts Payable Information System